Chloramphenicol Residues and Bacterial Contamination in Farmed African Catfish (Clarias gariepinus) from Banyuwangi Traditional Markets: A Risk Assessment - Ulkhaq, Mohammad Faizal; Kenconojati, Hapsari; Budi, Darmawan Setia; Pardede, Maria Agustina; Loh, Jiun-Yan (Jurnal Medik Veteriner, 2024)
This study aimed to determine chloramphenicol residues and bacterial contamination (Aerobic Plate Count-APC, Escherichia coli count, Salmonella sp., and Vibrio cholerae) in farmed African catfish (Clarias gariepinus) that are marketed in Banyuwangi, Indonesia. A total of ninety samples of C. gariepinus were collected from several markets in Banyuwangi, namely, Kertosari, Blambangan, and Banyuwangi Kota. Using standard procedures, APC, E. coli count, Salmonella sp., V. cholerae, and chloramphenicol residues were determined. 36.37% of samples from Kertosari markets; 23.33% of samples from Banyuwangi Kota markets; and 16.67% of samples from Blambangan markets contained chloramphenicol residues, but less than 0.3 ppb. Only 40% of samples from Kertosari markets, 36.67% of samples from Banyuwangi Kota markets, and 26.67% of samples from Blambangan markets were contaminated by E. coli, but were less than 3 MPNg-1. The highest APC was from Banyuwangi Kota, followed by Kertosari and Blambangan. No samples were contaminated by Salmonella sp. and V. cholerae from any of the markets, and there was no significant difference between all markets in APC, E. coli count, or chloramphenicol residues. All farmed catfish marketed in Banyuwangi were safe to eat because no samples exceeded the maximum chloramphenicol residue and bacterial contaminant standards. Further studies are needed to detect other antibiotic residues used in aquaculture, including tetracycline, sulphonamide, enrofloxacin, and nitrofuran.